COURSE OF EPILEPTIC SEIZURES IN PATIENTS AFTER TRAUMATIC BRAIN INJURY: CLINICAL OBSERVATIONS OF 23 CASES - Aliev Mansur Abdukholikovich (Research Focus International Scientific Journal, 2025)
Post-traumatic epilepsy (PTE) is one of the most disabling long-term complications of traumatic brain injury (TBI). Despite progress in acute neurotrauma care, epileptic seizures remain a major cause of morbidity, drug resistance, and impaired quality of life among survivors. Objective: To analyze the course, clinical features, and outcomes of epileptic seizures in patients with TBI. Methods: A total of 23 patients with post-traumatic seizures were observed for a mean follow-up of 24 months. Clinical data, electroencephalography (EEG), and neuroimaging findings were assessed. Seizures were classified according to the International League Against Epilepsy (ILAE 2017). Treatment outcomes and the rate of drug-resistant epilepsy (DRE) were evaluated. Results: Early post-traumatic seizures occurred in 30.4% of patients, while late seizures predominated (69.6%). Generalized tonic–clonic seizures were the most frequent type (51.2%). EEG abnormalities were present in 78.3% of cases, most often localized to the temporal lobes. Cortical contusions and hematomas were the leading imaging correlates. Levetiracetam was the most commonly prescribed antiepileptic drug (60.8%). Seizure control was achieved in 65.2% of patients, whereas 34.8% developed DRE. Psychiatric comorbidities (depression and anxiety) were reported in 26.1%. Conclusion: Epileptic seizures after TBI are predominantly late in onset and frequently associated with temporal lobe lesions. Approximately one-third of patients develop drug resistance, underscoring the need for early risk stratification, individualized therapy, and preventive strategies to reduce the burden of PTE.